The undrained shear strength of soft clay reinforced with group encapsulated lime bottom ash columns - Muzamir, Hasan; Wan Nursyafiqah, Wan Jusoh; Wong, Suk Chee; Hyodo, Masayuki (GEOMATE International Society, 2018)
This research was aimed to investigate the role of group encapsulated lime bottom ash columns in improving the shear strength by using laboratory scale model. Kaolin was being used as soil sample and lime bottom ash as the reinforced columns. The reinforc ed kaolin samples were tested by using Unconfined Compression Test (UCT). A total 7 batches of kaolin sample had been tested and each batch consist of 3 specimens represent sample without lime bottom ash column, partially penetration and fully penetration for group lime bottom ash columns. The specimen used was 50 mm i n diameter and 100 mm in height . The height of the group columns was 60 mm, 80 mm and 100 mm with 10 mm and 16 mm column diameter . The group encapsulated lime bottom ash columns was installed in the triangular pattern, as it was much easier to maintain the location of installed columns and the spacing in between the columns. The improvement of shear strength of group encapsulated lime bottom ash columns with area replacement ratio of 12.00 % (1 0 mm column diameter) and 30.72 % (16 mm column diameter) was 29.00 %, 44.17 %, 29.75 % and 1.00 %, 3.92 %, 7.33 % at sample penetration ratio, H c /H s of 0.6, 0.8 and 1.0 respectively. It can be concluded that the shear strength of soft clay could be improv ed by the installation of group encapsulated lime bottom ash columns. However, the improvement of shear strength of 10 mm group encapsulated lime bottom ash columns was increased more significant compared to 16 mm group encapsulated lime bottom ash columns .